Development of energy-saving technology for maintaining the functioning of heat pump power supply - Chaikovskaya, Eugene (Eastern-European Journal of Enterprise Technologies, 2018)
An integrated system of maintaining functioning of heat pump power supply based on prediction of a change of local water temperature was developed. A change in refrigerant vapor flow rate, the number of rotations of the electric motor of the compressor occurs at measuring of the refrigerant temperature at the outlet of the condenser, evaporation pressure, condensation pressure and voltage frequency. Comprehensive mathematic modeling of the heat pump system, based on the integrated system of maintaining soil heat discharge at the level of 8–10 °C was performed. Refrigerant flow rate, compressor motor power, voltage, voltage frequency, the number of rotations of electric motor of the compressor, coefficients of efficiency of a heat pump system for the established levels of functioning were determined. Parameters of convective heat exchange in the condenser, time constants and coefficients of the mathematical models of dynamics of a change in local water temperature, refrigerant flow rate, the number of rotations of the electric motor of the compressor were established. The functional estimation of a change in local water temperature in the range of 35–55 °C within the heating season, refrigerant vapor flow rate, the number of rotations of the electric motor of the compressor was obtained. Determining of the resulting functional information allows makes it possible to obtain the following advancing decisions: to maintain a change in evaporation pressure to change the refrigerant vapor flow rate for digital control; to maintain a change in evaporation pressure to change the refrigerant vapor flow rate and to change voltage frequency on a change of the number of rotations of the electric motor of the compressor for frequency control. That is why prediction of a change in local water temperature based on measurement of the refrigerant temperature at the outlet of the condenser was proposed. This estimation in the ratio with the measured evaporation pressure is included in analytical determining of refrigerant flow rate and the number of rotations of the electric motor of the compressor. Obtaining such estimation and measurement of frequency voltage makes it possible to make an advancing influence on coordination of functioning of the internal and external circuits of a heat pump system both at digital and frequency control.